Social Justice and the Future of Healthy Families: Sociocultural Changes and Challenges. Issue 3 (12th April 2019) - Russell, Stephen T.
Abstract : Given the pace of social changes, meanings of "family" and what makes a family healthy are changing. How can these changing meanings and understandings contribute to social justice for all families? First, I acknowledge how my personal history has intersected with research I do on youth and families. I define social justice with respect to healthy families, and then consider how contemporary scholarship helps define, redefine, and refine what is meant by "family." Examples are presented from research on cultural influences on parenting; parenting in same‐sex couple or lesbian, gay, bisexual, transgender, or queer (LGBTQ) families; and coming out in adolescence as LGBTQ. These examples illustrate how the notion of family is defined, redefined, and refined to provide new vantage points on the complexities, possibilities, and potential for social justice among contemporary families, especially those that are marginalized.